A Rural Community’s Livelihood Dynamic in the maintenance of a Mangrove Area as a Tourist Destination - Fitrianto, Achmad Room; Samsuri, Andriani (ASEAN Journal of Community Engagement, 2021)
This study identifies the problems faced by the residents of Banyuurip village and their adaptation efforts in preserving their mangrove areas. This paper aims to portray the community behavior dynamic in conserving the environment in line with the growth of pop culture in the social media era. Three components will be examined: first, the way people behave toward their environment; second, the economic pressure and the resources maximizing process, and the last component being the environmental issues that are framed in local political ecology. This paper uses the following five phases identified by the Sustainable Livelihood Framework (SLF): identifying vulnerabilities in the community, mapping the livelihood assets of the community, observing the transformation of structures and processes, identifying strategies implemented by the community, and formulating solutions. The SLF approach is useful for removing traditional barriers and is able to evaluate and modify the approach taken to follow the latest trends in society, by enriching the information gathered through this participation. This paper’s findings maintain that the mangrove conservation area in Banyuurip Village reassures the community of its potential use as conservation land and an alternative source of livelihood. However, the manpower required to conserve the mangrove consists mainly of senior residents and is partially supported by the younger generation. Conserving mangroves requires a lot of funds and is an arduous process. It requires support from several parties, such as local companies, mining companies, universities, government agencies, and others.